PENGARUH KEPADATAN DAN KADAR AIR TERHADAP HAMBATAN PENETRASI SONDIR PADA TANAU LANAU (Studi kasus: Lanau di Tondo Kota Palu) - Bontong, Benyamin (MEKTEK, 2009)
The penatration resistance using DCPT on a type of soil are influenced by density and moisture content. The aim of this research is to experimentally study of cone penetration resistance (qc) friction ratio Rf ), dry density (Î³d) and water content (w) relationship on silt. The silt sample taken from Tondo, Eastward of SMUN 5 Palu. The penetration test are worked on several Î³d and w variation. Test result showed that the higher the water content, the higher the friction ratio Rf but the lower the qc. At low w, the higher the Î³d the higher the gradient qc/w. At hight water content, rising up the Î³d have no significant influence to the gradient qc/w